ANALYSIS OF PROJECT-BASED LEARNING MODEL ON RECYCLING USED BOTTLES TO ENHANCE CRITICAL THINKING SKILLS AND ECOPRENEURSHIP SKILLS IN ELEMENTARY SCHOOL STUDENTS - Moh Saiful Bahri; Umi Mahmudah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This research is a literature review that aims to investigate the project-based learning modelof recycling used bottles and its potential in improving critical thinking skills and ecopreneurship skills in elementary school students. The research method used is the literature method, in which the author searches and analyzes related studies that have been conducted previously. Some aspects discussed in this literature review include project-based learning, recycling concepts, critical thinking skills development, ecopreneurship empowerment, and effective pedagogical approaches. In this literature review, the author identifies and analyzes various studies that have been conducted on the used bottle recycling project-based learning model and its impact on critical thinking skills and ecopreneurship skills in elementary school students. The author also evaluates the advantages and disadvantages of this learning method as well as the factors that can affect its effectiveness. The results of this literature review indicate that the used bottle recycling project-based learning model can be effective in improving critical thinking skills and ecopreneurship skills in elementary school students. Several studies noted that this learning model can improve students' understanding of the importance of recycling and its impact on the environment.This literature review has important implications in the context of environmental education inprimary schools. The information found in this literature review can serve as a foundation for educators and researchers to design and develop learning models that are effective in improving critical thinking skills and ecopreneurship skills in students.